Sex Differences in Attentional Selection Following Gaze and Arrow Cues - Chacón-Candia, Jeanette A.; Lupiáñez, Juan; Casagrande, Maria; Marotta, Andrea (Frontiers in Psychology, 2020)
Although the majority of literature has shown undistinguishable attentional effects when eye-gaze and arrows are used as cues, recent research has found that whereas eye-gaze selectively orient attention to the specific location or part of the object looked at, arrows unselectively direct attention towards parts of the environment. However, it is unclear whether this dissociation between gaze and arrow cues is related to social cognitive mechanisms such as the attribution of mental states (Theory of Mind, ToM). We aimed at replicating the dissociation between gaze and arrow cues and investigating sex differences in attentional object selection triggered by these two types of stimuli. While we replicated the arrow-gaze dissociation, this was equivalent in the male and female population. This finding seems to run counter the intuition that theory of mind abilities can account for the dissociation observed between gaze and arrow cues since greater ToM abilities have been generally shown in females. However, this conclusion it must be interpreted with caution since no differences in ToM abilities and autistic quotient scores were observed between male and female in our sample. Further research is needed to shed light on this issue.